Krüppel-Like Factor 6 Downregulation Is Connected with a Poor Prognosis and Tumor Growth in Non-Small-Cell Lung Cancer. (30th January 2022) - Zeng, Binbin; Lin, Jiaxin; Cai, Xingdong; Che, Li; Zeng, Wei; Liu, Shengming
Abstract : Purpose . Research in this article was performed to explore the biological role and clinical significance of Krüppel-like transcription factor 6 (KLF6) in non-small-cell lung cancer (NSCLC). Methods . KLF6 expression in NSCLC cell lines was analyzed using reverse transcription PCR and Western blot. The expressed KLF6 protein was examined in 50 surgical NSCLC tissues using immunohistochemistry. Statistical analyses were employed for clinical association examinations. CCK8 assay and Annexin V/PI analysis were used to execute cell proliferation and apoptosis in KLF6-overexpression cell lines and the control groups. Cleaved caspase-3 expression was also detected in KLF6-overexpression cells and NSCLC tissues. KLF6 expression correlation with cleaved caspase-3 was also examined. Results . It was discovered that downregulation of KLF6 was seen in human NSCLC cell lines. Low KLF6 expression in NSCLC tissues was correlated with poor patient prognosis (P < 0.005 ); patients with less KLF6 expression possessed a lower cumulative 5-year survival rate. Multivariate analysis showed KLF6 expression as an independent prognostic indicator for NSCLC individuals. Expression levels of KLF6 were associated with NSCLC tumor size (P = 0.041 ). Overexpression of KLF6 inhibited cell proliferation and stimulated A549 and H322 cell line apoptosis. Cleaved caspase-3 protein had higher expression levels in KLF6-overexpressed cells than in the control group. The KLF6 expression levels were positively related to the cleaved caspase-3 protein expression in NSCLC tissues (r = 0.689, P = 0.001 ). Conclusions . The results indicate that downregulation of KLF6 is a significant NSCLC progression marker. KLF6 prevents cell growth and promotes cell apoptosis, possibly caspase-3 activations.